2015
DOI: 10.1073/pnas.1507760112
|View full text |Cite
|
Sign up to set email alerts
|

Regulated proteolysis of a cross-link–specific peptidoglycan hydrolase contributes to bacterial morphogenesis

Abstract: Bacterial growth and morphogenesis are intimately coupled to expansion of peptidoglycan (PG), an extensively cross-linked macromolecule that forms a protective mesh-like sacculus around the cytoplasmic membrane. Growth of the PG sacculus is a dynamic event requiring the concerted action of hydrolases that cleave the cross-links for insertion of new material and synthases that catalyze cross-link formation; however, the factors that regulate PG expansion during bacterial growth are poorly understood. Here, we s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

13
184
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 126 publications
(214 citation statements)
references
References 43 publications
13
184
1
Order By: Relevance
“…While this might imply a high degree of functional redundancy, it does not exclude the possibility that some or all of these enzymes may have unique functions under other more specific conditions. A recent study (Singh et al 2012) confirmed muramyl endopeptidase activity for three additional E. coli proteins; Spr, YebA and YdhO, renamed in E. coli to MepS, MepM and MepH (Singh et al 2015). More specifically the study presented data implying that Spr or YebA might represent endopeptidases with less redundant functions in that it was feasible to construct an Δ sprΔyebA mutant only in an E. coli strain genetically complemented with spr (mepS) (Singh et al 2012).…”
Section: Introductionmentioning
confidence: 74%
See 1 more Smart Citation
“…While this might imply a high degree of functional redundancy, it does not exclude the possibility that some or all of these enzymes may have unique functions under other more specific conditions. A recent study (Singh et al 2012) confirmed muramyl endopeptidase activity for three additional E. coli proteins; Spr, YebA and YdhO, renamed in E. coli to MepS, MepM and MepH (Singh et al 2015). More specifically the study presented data implying that Spr or YebA might represent endopeptidases with less redundant functions in that it was feasible to construct an Δ sprΔyebA mutant only in an E. coli strain genetically complemented with spr (mepS) (Singh et al 2012).…”
Section: Introductionmentioning
confidence: 74%
“…In this, we selected and genetically confirmed that Δ spr-mediated vancomycin sensitization, even the more pronounced sensitization of the Δ sprΔyebA mutant, required a tsp-proficient genetic background. The gene tsp itself codes for periplasmic endopeptidase implicated in processing of Spr and PBP3 (Singh et al 2015;H Hara et al 1991;H. Hara et al 1989).…”
Section: Discussionmentioning
confidence: 99%
“…The EMBO Journal Proteolytic activation of PG hydrolase Helene Botella et al (Singh et al, 2015). However, unlike the action of MarP on RipA, PrC controls the level of MepS in E. coli by degrading it when it is no longer needed, such as in stationary phase.…”
Section: Discussionmentioning
confidence: 99%
“…Much less is known about EP regulation in Gram-negative bacteria, where EPs appear to be kept in check as part of multiprotein complexes (40, 41), at the transcriptional level (42, 43) or via proteolytic degradation (44, 45). Proteolytic turnover appears to be the major mode of regulation of growth-promoting EPs (44, 45); however, phenotypes associated with the accumulation of EPs have surprisingly mild phenotypes under normal growth conditions, suggesting an additional, unexplored layer of regulation.…”
Section: Introductionmentioning
confidence: 99%
“…The Gram-positive bacterium Bacillus subtilis (and likely other Gram-positive species as well) regulates EP activity via interactions with FtsEX and the PG synthesis elongation machinery (3537) and additionally encodes a post-translational negative regulator, IseA (YoeB) (38), which presumably serves to tone down EP activity during cell wall stress conditions (38, 39). Much less is known about EP regulation in Gram-negative bacteria, where EPs appear to be kept in check as part of multiprotein complexes (40, 41), at the transcriptional level (42, 43) or via proteolytic degradation (44, 45). Proteolytic turnover appears to be the major mode of regulation of growth-promoting EPs (44, 45); however, phenotypes associated with the accumulation of EPs have surprisingly mild phenotypes under normal growth conditions, suggesting an additional, unexplored layer of regulation.…”
Section: Introductionmentioning
confidence: 99%